2020
DOI: 10.1186/s13033-020-00406-2
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders' perceptions of child and adolescent mental health services in a South African district: a qualitative study

Abstract: Background In order to develop a district child and adolescent mental health (CAMH) plan, it is vital to engage with a range of stakeholders involved in providing CAMH services, given the complexities associated with delivering such services. Hence this study sought to explore multisectoral dynamics in providing CAMH care in one resource-constrained South African district as a case study, towards informing the development of a model for district mental health plan and generating lessons for men… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Our findings also concur with broader South African and international literature. For instance, a qualitative study that explored multistakeholders' perceptions of CAMHSS in another South African province (KwaZulu-Natal) found that there was a shortage of CAMH resources (human and infrastructure) resulting in service providers being overwhelmed with their workload, inadequate CAMH training for non-specialists, lack of a coordinated system of CAMH, and stigmatisation of mental illness in children and adolescents [19]. In an international systematic review that explored primary care practitioners' perceptions of the barriers to the effective management of CAMH problems, the authors found lack of staff training, lack of prioritisation of mental health problems, lack of resources, and family issues as key barriers [20].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also concur with broader South African and international literature. For instance, a qualitative study that explored multistakeholders' perceptions of CAMHSS in another South African province (KwaZulu-Natal) found that there was a shortage of CAMH resources (human and infrastructure) resulting in service providers being overwhelmed with their workload, inadequate CAMH training for non-specialists, lack of a coordinated system of CAMH, and stigmatisation of mental illness in children and adolescents [19]. In an international systematic review that explored primary care practitioners' perceptions of the barriers to the effective management of CAMH problems, the authors found lack of staff training, lack of prioritisation of mental health problems, lack of resources, and family issues as key barriers [20].…”
Section: Discussionmentioning
confidence: 99%
“…While we were not able to include voices of service users from rural districts in the Western Cape, the themes that emerged for the urban area of Cape Town, showed many similarities with ndings in the Amajuba rural district of KwaZulu-Natal (KZN), where Babatunde and colleagues recently conducted a situational analysis (31) and collected stakeholder perspectives. In their investigation of health, education, non-pro t organisations and service users, emerging themes included lack of services, poor coordination, lack of intersectoral work and low prioritisation of CAMH work.…”
Section: Create Separate Services For Child and Adolescent Mental Healthmentioning
confidence: 99%
“…In their investigation of health, education, non-pro t organisations and service users, emerging themes included lack of services, poor coordination, lack of intersectoral work and low prioritisation of CAMH work. The stakeholder study combined ndings for providers and service users, so it was not possible to do a direct comparison between the two studies, but illustrative quotes from the KZN study included comments about the need for information and parent education, and some positive examples of good care and support to families (31). One very interesting theme that emerged from the KZN study was the important role of schools and the Department of Education as partner in the early identi cation and treatment of child and adolescent mental health problems.…”
Section: Create Separate Services For Child and Adolescent Mental Healthmentioning
confidence: 99%
“…However, the implementation pace of these policies at the grassroots level is concerning, with no evidence thereof in any of the country's nine provinces [17]. Furthermore, mental health programmes for children and adolescents are also concerning in South Africa, where there is no evidence of procedures and protocols for CAMH disorders [19]. The implication is that intervention strategies that are currently designed and implemented may not have scienti c basis.…”
Section: The Status Of Camh In South Africamentioning
confidence: 99%
“…It is clear from the narratives that CAMH disorders and their social workers face many obstacles when accessing mental health services from hospitals. South-African studies [19,12] attested to this by pointing to CAMH disorder services that are underprovided and ineffective. A South African analysis of CAMH disorder services found a limited number of psychiatrists dedicated to CAMH disorders [39].…”
Section: Theme 4: Inaccessible Resources For Camh Disordersmentioning
confidence: 99%